2015
DOI: 10.1016/j.virusres.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Korean porcine epidemic diarrhea virus strain KNU-141112

Abstract: Severe outbreaks of porcine epidemic diarrhea virus (PEDV) have re-emerged in Korea and rapidly swept across the country, causing tremendous economic losses to producers and customers. Despite the availability of PEDV vaccines in the domestic market, the disease continues to plague the Korean pork industry, raising issues regarding their protective efficacy and new vaccine development. Therefore, PEDV isolation in cell culture is urgently needed to develop efficacious vaccines and diagnostic assays and to cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(123 citation statements)
references
References 36 publications
11
112
0
Order By: Relevance
“…The five US strains were reported to belong to North American clades I and II, following the PEDV outbreak in April 2013 (Vlasova et al., ). The three Korean strains are thought to be co‐circulating in Korea and showed high homology with the five US strains (Choi et al., ; Lee et al., ). The 31 isolated strains occupied all the 13 cities, suggesting that G3 was the most prevalent genotype in Shandong Province (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The five US strains were reported to belong to North American clades I and II, following the PEDV outbreak in April 2013 (Vlasova et al., ). The three Korean strains are thought to be co‐circulating in Korea and showed high homology with the five US strains (Choi et al., ; Lee et al., ). The 31 isolated strains occupied all the 13 cities, suggesting that G3 was the most prevalent genotype in Shandong Province (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pig population in Korea has plummeted due to a foot-and-mouth disease (FMD) outbreak in 2010-2011. As a consequence of strict biosecurity measures and a decreased pig population, outbreaks of PEDV have been attenuated (Lee et al, 2015). Even with the reduction of PEDV outbreaks in domestic pigs in this period, wild boar strains of PEDV were still detected.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical samples of aborted foetuses and dead pigs that suffered from severe diarrhoea and atrophy before dying from five different unvaccinated swine farms during 2017–2018 outbreaks were independently submitted for laboratory analysis (Table S1). Tissue specimens including tonsil, lymph node, spleen and lung were taken from each carcass, and all samples were prepared into 10% suspensions as described previously (Lee, Kim, & Lee, ). The initial combined RT‐PCR and sequencing analysis of CSFV 5′‐UTR showed that these samples were positive for LOM (Kim et al., ).…”
Section: Methodsmentioning
confidence: 99%